Development of the Integrated multi-trophic aquaculture (IMTA) System in the World; Article Review - Muhammad Hanif (Airlangga University, 2022)
Aquaculture is a sector of activity in the world that has grown very rapidly in the last few decades. Aquaculture is a food activity sector that aims to provide human food needs, especially protein. However, currently, aquaculture is required not only to be able to meet the protein needs of humans but also to be environmentally friendly and sustainable. IMTA is a system that aims to answer these aquaculture challenges. Currently, fish farming using the IMTA system in the world continues to grow. Many studies have been carried out, such as the selection of suitable species, efficient cultivation design to economic value in fish farming activities using the Ä°MTA system. Keywords: Aquaculture, challenges, IMTA system